THE COMMUNITY EMPOWERMENT THROUGH THE ROAD & ROLE MAP MODEL OF SUSTAINABLE ISLAMIC BOARDING SCHOOL BUSINESS RESILIENCE BASED ON A GREEN ECONOMY AT THE DAARUL ULUUM ISLAMIC BOARDING SCHOOL, JATINANGOR - Nur, Tajuddin; Rustiman, Uus (International Journal of Engagement and Empowerment (IJE2), 2023)
This community service activity aims to introduce the Road&Role Map Model for Community Empowerment Through Sustainable Islamic Boarding School Business Resilience Based on a Green Economy at the Daarul Uluum Islamic Boarding School, Jatinangor. At the Daarul Uluum Islamic boarding school in Jatinangor, this community service is carried out with the assistance of PAR. It consists of socialization, training, and assistance for teachers, students, and congregation members about community empowerment through sustainable Islamic boarding school business resilience based on a green economy. By utilizing Infocus and a projector, the material is presented in the form of a PowerPoint presentation. The results of the activities carried out on November 18 2023, found that teachers, students and congregations for community empowerment through sustainable Islamic boarding school business resilience based on a green economy at the Daarul Uluum Jatinangor Islamic boarding school were more enthusiastic and motivated to recognize the Road Map & Role model for Islamic boarding school business resilience Sustainable Green Economy Based, further in its application and implementation in daily life, especially for the congregation at the Daarul Uluum Jatinangor Islamic Boarding School. As a result of this community service activity, it is possible to conclude that this outreach activity has the potential to increase enthusiasm and high motivation to recognize further the Arabic Hajj & Umrah Digital Application for Teachers, Santri and Jama'ah Road Map & Role Model for Community Empowerment Through Resilience-Based Sustainable Islamic Boarding School Business Green Economy at the Daarul Uluum Jatinangor Islamic Boarding School. The participants' enthusiasm was a defining characteristic of the event